An integrated TAM, IDT, trust, service quality and UI/UX in explaining mobile banking adoption in Cambodia - Ratha Seng; Rady Chhun; Sengtha Chay; Bunnak Poch (Southeast Asian Journal of Service Management, 2026)
This research investigates the determinants of mobile banking adoption in Cambodia using a convergent mixed-methods design. The study integrates TAM, IDT, Trust and Service Quality constructs to explain behavioral intention. Quantitative data were obtained from 528 university students and analyzed through PLS-SEM, while qualitative insights were gathered from 10 SME owners to assess practical experiences with mobile banking applications, particularly UI/UX features and Bakong-enabled transactions. Empirical results indicate that Perceived Ease of Use, Trust, Service Quality and Customer Satisfaction are the most significant predictors of Behavioral Intention. In contrast, Perceived Usefulness, Complexity, and Security do not exert direct significant influence within this context. The qualitative findings complement the statistical results by highlighting users’ preference for simple navigation, efficient QR scan, and secure transaction confirmation. The study concludes that technological reliability and positive user experience are more decisive than functional benefits alone. The integrated framework provides both theoretical contribution and practical implications for financial institutions seeking to enhance digital banking adoption and strengthen Cambodia’s digital financial ecosystem.